Bearing-based formation manoeuvring control of multi-agent systems with constant communication delays. (28th March 2021) - Zhao, Jianing; Yu, Xiao
This paper investigates the bearing-based formation manoeuvring control problem of multi-agent systems with constant communication delays. Leaders move with time-varying velocities, and followers aim to track leaders' motion and form a bearing-defined moving desired formation. A dynamic controller for each follower is developed based on its position, velocity, its neighbours' position, velocity, acceleration. The motion information of neighbours is obtained via communication, and communication delays are taken into account. Then a rigorous proof is provided to show that tracking errors of the neutral-type system are globally uniformly ultimately bounded. Finally, simulation results are presented to illustrate the effectiveness.